Hollow Co3O4 nanospheres for the direct electrochemistry and electrocatalysis of hemoglobin with an ionic liquid as an enhancer. Issue 16 (21st August 2015) - Zeng, Yan; Zhang, Huanhuan; Wu, Xu; Ke, Yan; Qu, Pingping; Zhu, Zhihong
<x xml:space="preserve">Abstract</x> Hollow Co3O4 nanospheres were synthesized via a hydrothermal process and applied to fabricate a redox protein-based sensing platform.